Pengaruh Profitabilitas Dan Inflasi Terhadap Nilai Perusahaan(Studi Perusahaan Manufaktur Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2023) - Amara Octaviani; Enji Azizi; Didi Wandi (Indonesia Economic Journal, 2026)
This study aims to analyze the effect of profitability and inflation on firm value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. Profitability is measured using Return on Assets (ROA), while firm value is measured using Price to Book Value (PBV). The research employs a quantitative approach with a purposive sampling method, resulting in a sample of 22 companies. Data analysis was conducted with the help of SPSS Version 20. The partial test results show that the profitability variable (X1) has a negative and significant effect on firm value (PBV), as indicated by a significance value of 0.000, which is smaller than the α level of 0.05, and a t-value of -42.681, which is greater than the t-table value of 1.97190. The partial test results also indicate that the inflation variable (X2) has a negative and significant effect on firm value (PBV), as shown by a significance value of 0.000, which is below the required significance level of 0.05, and a t-value of - 77.227, which exceeds the t-table value of 1.97190. Simultaneously, profitability (ROA) and inflation have a significant effect on firm value (PBV).